2012
DOI: 10.1074/jbc.m111.297887
|View full text |Cite
|
Sign up to set email alerts
|

β-Glucan from Lentinus edodes Inhibits Nitric Oxide and Tumor Necrosis Factor-α Production and Phosphorylation of Mitogen-activated Protein Kinases in Lipopolysaccharide-stimulated Murine RAW 264.7 Macrophages

Abstract: Background: High level of NO and TNF-␣ can induce diverse effects on host survival. Results: Lentinan inhibits NO and TNF-␣ secretion and phosphorylation of MAP kinases JNK1/2 and ERK1/2. Conclusion: Inhibition of NO and TNF-␣ is partially through suppression of JNK1/2 and ERK1/2 activation. Significance: A novel pharmacological molecule is discovered to control the diseases associated with NO and TNF-␣ overproduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(30 citation statements)
references
References 73 publications
1
28
0
1
Order By: Relevance
“…In vivo fungal β-glucans mostly elicit anti-inflammatory, anti-oxidant and anti-tumour effects [25]. Lentinan from shiitake can regulate MAP kinases JNK1/2 and ERK1/2 and enhance the nuclear translocation of NF-κB but without NO and TNF-α production in RAW 264.7 cells [26,27]. …”
Section: Discussionmentioning
confidence: 99%
“…In vivo fungal β-glucans mostly elicit anti-inflammatory, anti-oxidant and anti-tumour effects [25]. Lentinan from shiitake can regulate MAP kinases JNK1/2 and ERK1/2 and enhance the nuclear translocation of NF-κB but without NO and TNF-α production in RAW 264.7 cells [26,27]. …”
Section: Discussionmentioning
confidence: 99%
“…The development of the inflammatory process involves the production of pro-inflammatory cytokines and inflammatory mediators, such as tumor necrosis factor α (TNF-α), interleukin 1β (IL-1β), nitric oxide (NO) and prostaglandin E2 (PGE2), which are the main factors that mediate the LPS-induced toxic effects [9][10][11]. The inhibition of the excess production of pro-inflammatory factors is required for decreasing inflammatory reactions, which are the main cause of inflammatory diseases.…”
Section: Introductionmentioning
confidence: 99%
“…As described in Materials and Methods, the chemical analysis has indicated that LE is chiefly made up of polysaccharides, which have been demonstrated to exhibit significant biological effects such as anti-inflammatory and anti-oxidative activity in previous reports [32,33]. In addition, several researchers have revealed that lentinan, β-glucan from Lentinus edodes, induces immunomodulatory and immunosuppressive behaviors under different conditions through MAPK signaling pathways mediated by ERK1/2 and JNK1 /2 [3,5]. Furthermore, the recent study provides evidence that lentinan could inhibit gut inflammation via modulation of NF-κB activity in the experimental models [34].…”
Section: Discussionmentioning
confidence: 99%